The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphys.2019.00198
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Photoplethysmographic Waveform Characteristics: Effect of Measurement Site

Abstract: Introduction: Photoplethysmography (PPG) has been widely used to assess cardiovascular function. However, few studies have comprehensively investigated the effect of measurement site on PPG waveform characteristics. This study aimed to provide a quantitative comparison on this.Methods: Thirty six healthy subjects participated in this study. For each subject, PPG signals were sequentially recorded for 1 min from six different body sites (finger, wrist under (anatomically volar), wrist upper (dorsal), arm, earlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 25 publications
5
91
0
1
Order By: Relevance
“…Not surprisingly, we observed that the quality of pulse wave measurement is affected by the measuring site. The finding is consistent with those of Hartmann et al (2019). The stability of the pulse wave obtained from the carotid artery is worse than that of the radial artery (Adji et al, 2006).…”
Section: External Factors Influencing Sensor Performancesupporting
confidence: 88%
See 1 more Smart Citation
“…Not surprisingly, we observed that the quality of pulse wave measurement is affected by the measuring site. The finding is consistent with those of Hartmann et al (2019). The stability of the pulse wave obtained from the carotid artery is worse than that of the radial artery (Adji et al, 2006).…”
Section: External Factors Influencing Sensor Performancesupporting
confidence: 88%
“…An effective sensor must be robust, stable, and give reproducible signals. Many factors can affect their performance, including the way in which they are applied to the skin, the contact force between the sensor and the skin (Teng and Zhang, 2006), and the measuring site (Lukas et al, 2014;Hartmann et al, 2019). Therefore, we have analyzed the four sensors' susceptibilities to these external factors and compared their stability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Fingers, earlobes, forehead, and wrist are common PPG recording locations. Finger is the body site most used for clinical applications, being the most practical and the most sensitive to blood volume fluctuations [16][17][18]. From quantitative analysis of waveform characteristics, e.g., mean amplitude and peak point position, the forehead resulted to be related to the least analyzable PPG signal, whereas the finger and the earlobe were reported to be the locations which produce the most reliable PPG signals [17].…”
Section: Introductionmentioning
confidence: 99%
“…Finger is the body site most used for clinical applications, being the most practical and the most sensitive to blood volume fluctuations [16][17][18]. From quantitative analysis of waveform characteristics, e.g., mean amplitude and peak point position, the forehead resulted to be related to the least analyzable PPG signal, whereas the finger and the earlobe were reported to be the locations which produce the most reliable PPG signals [17]. The same results were found using statistical approaches, e.g., kurtosis and Shannon entropy, to automatically quantify the quality of multi-site PPG signals [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation